Progress Tracking Dashboard using React.JS Review - Faizan Raza Sheikh; Hrishabh V. Petkar; Ketan Komawar; Abdul Malik Sheikh; Devashri Raich (International Journal of Advanced Research in Science, Communication and Technology, 2024)
The Progress Tracking Dashboard built with React.js is a dynamic and user-friendly web application designed to empower users in monitoring, analyzing, and visualizing their progress across various domains. This dashboard harnesses the power of React.js, a popular JavaScript library for building interactive user interfaces, to provide an intuitive and responsive user experience. the Progress Tracking Dashboard built with React.js offers a robust solution for individuals and organizations seeking a versatile and efficient tool to monitor and analyze their progress in real-time. Leveraging React.js's capabilities, this dashboard provides an engaging and customizable user experience while ensuring data security and performance. Whether used for personal development, project management, or business analytics, this dashboard empowers users to make informed decisions and achieve their goals effectively.